Odpowiedź :
Odpowiedź:
1.
a) 2x – 7y + (5x – 2y) = 2x – 7y + 5x – 2y = 7x - 9y
b) 5a – (3a + 6 ) = 5a - 3a - 6 = 2a - 6
c) - 2x + 8y – (6x – 7y) = - 2x + 8y – 6x + 7y = - 8x + 15y
2.
a) -2 (3b – 4a + 0,5) = - 6b + 8a - 1 = 8a - 6b - 1
b) 3x (x + 2y – 8) = 3x² + 6xy - 24x
(-21m – 15) : 3 = - 7m - 5
(6x - 2y + 10)/2 = 3x - y + 5
3.
a) (2a - 3)(5 – b) = 10a - 15 - 2ab + 3b = 10a - 2ab + 3b - 15
b) (6 – 2x)(3x + 1) = 18x - 6x² + 6 - 2x = - 6x² + 16x + 6
Szczegółowe wyjaśnienie:
1.
a) 2x – 7y + (5x – 2y) = 2x – 7y + 5x – 2y = 7x - 9y
b) 5a – (3a + 6 ) = 5a - 3a - 6 = 2a - 6
c) - 2x + 8y – (6x – 7y) = - 2x + 8y – 6x + 7y = - 8x + 15y
2.
a) -2 (3b – 4a + 0,5) = - 6b + 8a - 1 = 8a - 6b - 1
b) 3x (x + 2y – 8) = 3x² + 6xy - 24x
(-21m – 15) : 3 = - 7m - 5
(6x - 2y + 10)/2 = 3x - y + 5
3.
a) (2a - 3)(5 – b) = 10a - 15 - 2ab + 3b = 10a - 2ab + 3b - 15
b) (6 – 2x)(3x + 1) = 18x - 6x² + 6 - 2x = - 6x² + 16x + 6